Israel and the bantustanization of Palestine - Iveković Ivan (Međunarodni Problemi, 2002)
Contrary to repeated statements that Israel is a 'democratic state,' the author argues that it is an ethnocratic state. From its inception it has established a system of legal, political, residential and economic segregation of its Palestinian citizens. Since Israel has occupied the West Bank, Jerusalem and the Gaza Strip in 1967, these were subjected to a systematic Jewish colonization and Judaization, which were met with Palestinian resistance. Both created a spiral of political violence. Israel's 'industrial' state terror is now confronted with 'artisan's'' terror of frustrated Palestinian groups. The author is of the opinion that a highly defective 'peace' deal offered by the Israeli government of Ariel Sharon would have transformed the Palestinian state entity in a Bantustan-like cluster of would-be 'autonomous areas'.